Relação entre lealdade de marca e os atributos de compra em lojas especializadas e lojas da fábrica - Parente, Ana Luisa Trajano (2014)
The study of brand loyalty allows companies operating in the brazilian retail to develop assertive strategies to maintain existing customers and attract new consumers. Based on this assumption, this research has the main objective to analyze the relationship between brand loyalty and the attributes of the choice of point of sale for children’s clothing. In order to examine this relationship, a quantitative survey consisting of 20 attributes related to the relationship between price and quality, product quality and store atmosphere. The study sample consisted of 201 mothers living in the city of Fortaleza, Ceará. The survey data were collected in November 2013 and submitted to statistical tests of factor analysis and multiple regression. From the statistical tests, it was identified that the 20 items surveyed, attributes more related to brand loyalty are: store image, product differentiation, product better than the competition, finishing the product and value for money.